The Role of Altruism, Islamic Spirituality and the Personality to the Subjective Well-Being of Working Mothers in the COVID-19 Pandemic - Mukaromah, Illiyyin Tri; Anganthi, Nisa Rachmah Nur (Universitas Muhammadiyah Surakarta, 2022)
The COVID-19 pandemic situation makes the burden of working women who have children increase and will affect subjective well-being. With the behavior of helping others, it can have a strong influence on increasing individual happiness. Spirituality makes life more meaningful so that individuals avoid stress and depression. Then the personality of the individual is able to influence the individual in viewing a problem so that it can have an impact on her subjective well-being. The purpose of this study was to examine the role of altruism, Islamic spirituality, and the personality on the subjective well-being of working mothers during the COVID-19 pandemic. The research method used is correlational quantitative. Collecting data using Satisfaction With Life Scale (SWLS) and Positive And Negative Affect Schedule (PANAS), altruism scale, Multidimensional Measure of Islamic Spirituality (MMS) scale, and Big Five Inventory (BFI) scale. The population in this study amounted to 4,375 people with a total sample of 323 people. The sampling technique used is convenience sampling. Data analysis using multiple regression with the help of SPSS version 23.0. for windows.The results showed that altruism, Islamic spirituality, and the five big five personality dimensions significantly contributed to the subjective well-being of working mothers during the pandemic with a significance level of 0.000 (p<0.05) with an effective contribution of 22.4%. Personality neuroticism is the biggest predictor that affects subjective well-being. The implication of this study is to increase insight into coping with anxiety and then provide training to reduce anxiety in working mothers during the pandemic.